2014
DOI: 10.1111/jwas.12136
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Stocking Density on Growth, Survival, and Condition of the Mexican Cichlid Cichlasoma beani

Abstract: The Mexican cichlid Cichlasoma beani is currently exploited regionally as food and can be commercialized in the aquarium trade. Natural populations of C. beani may already be negatively affected by anthropogenic alteration of the areas in which it is distributed. The aim of the present study was to examine the effect on growth, survival, and condition of C. beani cultured in three stocking densities: three (D3), six (D6), and nine (D9) fish per each 40 L tank. At the end of a 6‐wk trial the fish cultured in D3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
3
3
0
Order By: Relevance
“…In other native cichlids of commercial interest, Petenia splendida and M. urophthalmus, Jiménez-Martinez et al (2009) evaluated different stocking densities at the larvae stage (0.5, 1, 5, 10, and 20 larvae L -1 ) and observed that the average weight and length were higher in the lower densities of both species. These results, those of Aragón-Flores et al (2014) and the ones presented in this work support the idea that stocking density has a clear effect on growth during the early stages of development, especially in territorial and aggressive fish species like the members of the cichlid family. In these species, higher densities increase the competition for food, causing the strongest organisms (usually those of larger size) to feed first and restrict the small ones to feed, which is reflected in growth and survival (Álvarez-González et al 2001;Costa et al 2017).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In other native cichlids of commercial interest, Petenia splendida and M. urophthalmus, Jiménez-Martinez et al (2009) evaluated different stocking densities at the larvae stage (0.5, 1, 5, 10, and 20 larvae L -1 ) and observed that the average weight and length were higher in the lower densities of both species. These results, those of Aragón-Flores et al (2014) and the ones presented in this work support the idea that stocking density has a clear effect on growth during the early stages of development, especially in territorial and aggressive fish species like the members of the cichlid family. In these species, higher densities increase the competition for food, causing the strongest organisms (usually those of larger size) to feed first and restrict the small ones to feed, which is reflected in growth and survival (Álvarez-González et al 2001;Costa et al 2017).…”
Section: Discussionsupporting
confidence: 89%
“…This was probably caused by low food and territory competition, which allowed a higher consumption and assimilation of nutrients from the food. Similar results were observed, in terms of final weight and length, in the native cichlid Cichlasoma beani by Aragón-Flores et al (2014). These authors report that the treatment with the lower density resulted in heavier and larger fish, attributing it to the lack of competition, based on the aggression levels observed during feeding in the higher densities.…”
Section: Discussionsupporting
confidence: 75%
“…Riche et al (2013) concluded that stocking density does have a negligible effect in the condition of market size cobia (Rachycentron canadum). The poor effect of stocking density on the fish condition was consistent even in a study conducted by Aragón-Flores et al (2014), in which the authors (contrarily to the resulting tendency of the majority of the studies, where the lower the stocking density, the greater the growth) found greater growth and survival on the cichlid Cichlasoma beani cultured in relatively high densities.…”
Section: Benziesupporting
confidence: 65%
“…These studies also have been conducted using low intensification production systems such as floating cages and ponds. A few studies have shown that a low stocking density triggers a negative hierarchical interaction (Chakraborty & Banerjee, 2010;Shubha & Reddi, 2011;Aragón-Flores et al, 2014). Finding an adequate density contributes to the optimization of production systems.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, a study by [3] focused on the in situ reproductive population structure and its relation to the ecology of this species. Prior studies examined the effects of stocking density on growth and survival of this species under culture conditions [4,5]. There are currently no studies on biochemistry and digestive physiology of this species, although studies have been conducted on digestive biochemistry in species of the genus Cichlasoma [6][7][8], which contribute…”
Section: Introductionmentioning
confidence: 99%